1972
DOI: 10.1139/m72-169
|View full text |Cite
|
Sign up to set email alerts
|

Pectolytic and cellulolytic enzymes associated with Helminthosporium leaf spot on Kentucky bluegrass

Abstract: Using maceration, viscometric, and spectrophotometric tests, culture filtrates and extracts of healthy and Helminthosporium sativum-infected common and Merion Kentucky bluegrass foliage were tested for pectolytic and cellulolytic enzymes. Culture filtrates, in which pectin was the carbon source, exhibited polymethylgalacturonase and pectin methyl-trans-eliminase activity, with optima of pH 6–7 and pH 8, respectively. Extracts from diseased foliage of common and Merion Kentucky bluegrasses contained pectin meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

1972
1972
2001
2001

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…Da MOORE und STONE (1968) bei virusinfizierten Tabakpflanzen ebenfalls eine starke Erhohung der p-1,3-Glucanase-Aktivitat feststellen konnten, diirfte diesem Enzym nicht nur eine alterungsphysiologische, sondern auch eine allgemein strefibedingte Bedeutung zukommen. Daneben spielen Glykosidasen bei nekrotischen Prozessen eine gewisse Rolle; so sollen sie bei Infektionskrankheiten die Ausbreitung des Parasiten dureh Gewebezerstorung verhindern (MUSE et al 1972;REDDY et al 1973). Die Aktivitatszunahme einzelner Glykosidasen lie(5e sich somit als eine unspezifische Abwehrreaktion und als erste Zeichen spater sichtbar werdender Symptome deuten.…”
Section: Diskussion Und Folgerungenunclassified
“…Da MOORE und STONE (1968) bei virusinfizierten Tabakpflanzen ebenfalls eine starke Erhohung der p-1,3-Glucanase-Aktivitat feststellen konnten, diirfte diesem Enzym nicht nur eine alterungsphysiologische, sondern auch eine allgemein strefibedingte Bedeutung zukommen. Daneben spielen Glykosidasen bei nekrotischen Prozessen eine gewisse Rolle; so sollen sie bei Infektionskrankheiten die Ausbreitung des Parasiten dureh Gewebezerstorung verhindern (MUSE et al 1972;REDDY et al 1973). Die Aktivitatszunahme einzelner Glykosidasen lie(5e sich somit als eine unspezifische Abwehrreaktion und als erste Zeichen spater sichtbar werdender Symptome deuten.…”
Section: Diskussion Und Folgerungenunclassified
“…The importance of cellulolytic enzymes in the helminthosporiose diseases has been demonstrated by MUSE and COUCH (1969) in Kentucky blue grass infected by H. sorokinianum and by VIDHYASEKARAN et al (1971b) in sorghum infected by H. turcicum. LUMSDEN (1969) observed direct correlation between the presence of cellulase in diseased tissues and the severity of disease symptoms.…”
Section: Discussionmentioning
confidence: 96%
“…Pectolytic enzymes play an important role in helminthosporiose incidence (MUSE andCOUCH 1969, VIDHYASEKARAN et al 1971a). UNBEHAUN and MOORE (1970) reported that in the susceptible tissues, the pathogen produced more pectic enzymes than in the resistant tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Virulence of Helminthosporium spp. has been reported to depend upon the production of pectic enzymes (MUSE and COUCH 1969). NELSON and SHERWOOD (1968) reported that H. carbonum produced endopolygalacturonase.…”
Section: Discussionmentioning
confidence: 99%